The perils of altering incentive plans: A case study - Antti Kauhanen (The Research Institute of the Finnish Economy (ETLA), 2011)
This paper studies a retail chain that introduced a sales incentive plan that rewarded for exceeding a sales target and subsequently cut the incentive intensity in addition to increasing the target. Utilizing monthly panel data for 54 months for all 53 units of the chain the paper shows that the introduction of the sales incentive plan increased sales and profitability, while the changes in the plan lead to a marked drop in sales and profitability. Thus, modifying the incentive plan proved costly for the firm. The results are consistent with the gift-exchange model of labor contracts.
Keywords: M52; J33; M54; J53; 330; incentive pay; gift exchange; panel data; Leistungsentgelt; Austauschtheorie (Soziologie); Panel; Finnland